PENGARUH PEMBERIAN KOMPRES HANGAT DAN KOMPRES DINGIN TERHADAP NYERI SENDI PADA LANSIA DI POSYANDU LANSIA WILAYAH KERJA PUSKESMAS LEMPAKE SAMARINDA - Hesti Prawita Widiastuti (Poltekkes Kemenkes Kalimantan Timur, 2022)
Abstract Elderly people often complaint to have joint pain. There should be a pharmacological and nonpharmacological treatment for reducing joint pain in elderly. One of the non pharmacological therapy is compress, both heat or cold. This study aimed to know the effect of heat compress and cold compress for reducing joint pain in elderly. This study is using quasy experiment design with pre and post test without control. The sampling method is non probability sampling with purposive sampling. The amout of samples from each group are 10 people. Each intervention had been done for twice a week. The result of hypothesis tests with Paired T-Test that there an impact of heat compress to decreasing pain obtained p value 0,000, and from intervention cold compress had impact too to decreasing pain obtained p value 0,000. Both heat and cold compress have an impact to reducing pain. But according to difference mean value, decreasing value of heat compress with 2,45 have higher impact rather than cold compress which have 0,90. For the next researchers could add more characteristic of respondent that could be influential to pain alteration. Besides, for the next research could take a longer time for giving the interventions.